Does Internet Addiction Lead to Academic Procrastination among Pharmacy Students at a University in Türkiye? A Cross-Sectional Study - Ulutaş Deniz, Elif; Kamran Rasheed, Muhammad; Eren, Rümeysa (Addicta: The Turkish Journal on Addictions, 2025)
Pharmacy students belong to the age group with the highest use of the internet and they are at risk of unregulated and unnecessary internet addiction, which could have a negative impact on their learning behaviors, academic grades, and time management skills. This study aims to assess the time management skills, academic procrastination, and academic performance of pharmacy students in Türkiye and their relationship with internet addiction. A cross-sectional study was conducted among 622 pharmacy students in Türkiye. This study used Young’s Internet Addiction Test (IAT) Time Management Inventory (TMI) and Tuckman Procrastination Scale (TPS) to evaluate internet addiction, time management and academic procrastination respectively. According to the results, no significant differences were found in IAT scores based on gender (p = .096). The study findings also revealed a significant correlation between pharmacy students’ total IAT score and their overall TMI score. In contrast, there is a positive and moderately significant relationship observed between pharmacy students’ total IAT and TPS scores. And internet addiction significantly predicted academic procrastination. In light of the findings, the study suggested that academic institutions and relevant authorities need to promote responsible internet usage among pharmacy students to increase their academic performance.
Keywords: addiction; pharmacy; procrastination; time management; universities